Colletti bianchi Una ricerca nell'industria e la discussione dei suoi risultati - Ponzellini, Anna Maria; Cipriani, Alberto (Studi e saggi, 2019)
This volume presents the results of a research on clerks and managers in large companies of the engineering sector (at the FCA and Leonardo centres), which she conducted using a participatory research methodology. The survey aimed at analysing the changes in professionalism, organization, quality of work and relationship with the trade union in recent years with regard to the main employment domains (administration, commerce, research and development, production support), in the face of the progressive disappearance of a homogeneous professional and social identity of the employment world and of the new 4.0 technologies' growing impact. The research was conducted with qualitative (interviews and focus) and quantitative (a survey of workers) research methods, and revealed discussions and comparisons between researchers, social actors from the involved companies (trade unionists and managers) and a group of scholars who followed the whole process.